2020
DOI: 10.1016/j.lfs.2020.118312
|View full text |Cite
|
Sign up to set email alerts
|

Attaching clinical significance to COVID-19-associated diarrhea

Abstract: The Corona Virus Disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), erupted in 2020 and created severe public health and socioeconomic challenges worldwide. A subset of patients, in addition to presenting with typical features such as fever, cough and dyspnea, was also afflicted with diarrhea. However, the clinical features and prognoses related to COVID-19-associated diarrhea have not attracted sufficient attention. This review of the medical literature e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
(53 reference statements)
0
23
2
2
Order By: Relevance
“…Our population rarely suffered from gastrointestinal symptoms and this data contrast with an initial case report of Wang et al in which 80% of the patient presented with diarrhea. The reported incidence of diarrhea in patients with COVID-19 ranged from 2% to 49.5% in the literature [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our population rarely suffered from gastrointestinal symptoms and this data contrast with an initial case report of Wang et al in which 80% of the patient presented with diarrhea. The reported incidence of diarrhea in patients with COVID-19 ranged from 2% to 49.5% in the literature [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The link between diarrhea and abdominal pain and the antibody response is intriguing. SARS-CoV-2-induced diarrhea may directly exacerbate inflammation and disease severity (32). Thus, diarrhea simply may be a marker of severe disease, which is associated with higher antibody titers.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not see increased diarrhea in our hospitalized patients (Table 1). Another possibility is that diarrhea, which is typically caused by enteric viral infection and damage (32), may directly enhance the antibody response, perhaps by activating inflammatory cells throughout the gut. However, at this time, the mechanism by which diarrhea might enhance antibody titers is unknown and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study from COVID-19–positive patients in Hubei, China, revealed that 46% presented with gastrointestinal (GI) problems, such as vomiting, diarrhea, or abdominal pain early in the disease [ 23 , 24 ]. The most common digestive tract symptom in adults and children is diarrhea, with the reported incidence of diarrhea in patients with COVID-19 ranging from 2% to 49.5% [ 25 ]. The ACE2 receptor is highly expressed in the gastrointestinal tract and plays an important role in the control of intestinal inflammation and intestinal microbial ecology; when the ACE2 receptor is activated by SARS-CoV-2, it can cause inflammation (enteritis) and eventually diarrhea [ 23 , 25 , 26 ].…”
Section: The Gut Microbiome and Covid-19mentioning
confidence: 99%
“…The most common digestive tract symptom in adults and children is diarrhea, with the reported incidence of diarrhea in patients with COVID-19 ranging from 2% to 49.5% [ 25 ]. The ACE2 receptor is highly expressed in the gastrointestinal tract and plays an important role in the control of intestinal inflammation and intestinal microbial ecology; when the ACE2 receptor is activated by SARS-CoV-2, it can cause inflammation (enteritis) and eventually diarrhea [ 23 , 25 , 26 ]. Seventeen studies in China, the United States, and Singapore showed SAR-CoV-2 viral RNA has been detected in the stools of an average of 43% of COVID-19 patients [ 23 ].…”
Section: The Gut Microbiome and Covid-19mentioning
confidence: 99%